Psychoanalytical neuroscience: Exploring psychoanalytic concepts with neuroscientific methods - Henrik Kessler (Frontiers Research Topics, 2015)
Sigmund Freud was a trained neuroanatomist and wrote his first psychoanalytical theory in neuroscientific terms. Throughout his life, he maintained the belief that at some distant day in the future, all psychoanalytic processes could be tied to a neural basis: "We must recollect that all of our provisional ideas in psychology will presumably one day be based on an organic substructure" (Freud 1914, On Narcissism: An Introduction). Fundamental Freudian concepts reveal their foundation in the physiological science of his time, most importantly among them the concept of libidinous energy and the homeostatic "principle of constancy". However, the subsequent history of psychoanalysis and neuroscience was mainly characterized by mutual ignorance or even opposition; many scientists accused psychoanalytic viewpoints not to be scientifically testable, and many psychoanalysts claimed that their theories did not need empirical support outside of the therapeutic situation. On this historical background, it may appear surprising that the recent years have seen an increasing interest in re-connecting psychoanalysis and neuroscience in various ways: By studying psychodynamic consequences of brain lesions in neurological patients, by investigating how psychoanalytic therapy affects brain structure and function, or even by operationalizing psychoanalytic concepts in well-controlled experiments and exploring their neural correlates. These empirical studies are accompanied by theoretical work on the philosophical status of the "neuropsychoanalytic" endeavour. In this volume, we attempt to provide a state-of-the-art overview of this new exciting field. All types of submissions are welcome, including research in patient populations, healthy human participants and animals, review articles on some empirical or theoretical aspect, and of course also critical accounts of the new field. Despite this welcome variability, we would like to suggest that all contributions attempt to address one (or both) of two main questions, which should motivate the connection between psychoanalysis and neuroscience and that in our opinion still remain exigent: First, from the neuroscientific side, why should researchers in the neurosciences address psychoanalytic ideas, and what is (or will be) the impact of this connection on current neuroscientific theories? Second, from the psychoanalytic side, why should psychoanalysts care about neuroscientific studies, and (how) can current psychoanalytical theory and practice benefit from their results? Of course, contributors are free to provide a critical viewpoint on these two questions as well.